El tabaco (Nicotiana tabacum L.) nuevo hospedante de Rhizoglyphus setosus manson (Acari: Acaridae)en Cuba - Martinez Gutierrez, Z.=700 1 Mendez Gonzalez, R.; Sanchez, A.
(En, Es)
ilus., 3 ref.
Keywords: NICOTIANA TABACUM; RHIZOGLYPHUS SETOSUS; ACARIDAE; DAÑOS; SISTEMA RADICULAR; CUBA; RHIZOCLYPHUS SETOSUS